Diagnostic accuracy of ultrasonography in predicting urolithiasis for patients with hydronephrosis in comparison to computed tomography urography / Haidah Hidayah Humaidia, Khariah Mat Norb and Lyana Shahirah Mohd Yamin - Humaidi, Haidah Hidayah; Mat Nor, Khariah; Mohd Yamin, Lyana Shahirah (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
The main objective of this study was to evaluate the diagnostic accuracy of ultrasonography (US) in predicting urolithiasis and to answer whether there is a significant association between the presence of hydronephrosis with the presence of urolithiasis. This retrospective study involved radiology reports of 57 patients underwent both US of kidney, ureter and bladder (KUB) and computed tomography urography (CTU) examinations within 24 hours to each other and were selected based on inclusion criteria. Radiology reports of US and CTU were reviewed for the presence and degree of hydronephrosis, presence of calculi and location of calculi. The diagnostic accuracy was calculated using cross-tabulation function on SPSS and the association of presence of hydronephrosis and urolithiasis on CTU was analyzed using Chi-Squared test on SPSS with α=0.05. US had a sensitivity of 83.8%, specificity of 60%, positive predictive value (PPV) of 0.79 and negative predictive value (NPV) of 0.67 in predicting urolithiasis based on US findings of hydronephrosis in comparison to CTU. The presence of hydronephrosis was significantly associated with the presence of urolithiasis on CTU (chi square: 11.5, df= 1, p < 0.001). The ultrasound had diagnostic accuracy of 75% in predicting urolithiasis based on ultrasound findings of hydronephrosis. The presence of hydronephrosis was associated with the presence of urolithiasis. However, other factors that might affect the presence of hydronephrosis should be considered such as the stone location and size.